COVID-19 in Children: A Review and Parallels to Other Hyperinflammatory Syndromes - Hobbs, Charlotte V.; Khaitan, Alka; Kirmse, Brian M.; Borkowsky, William (Frontiers in Pediatrics, 2020)
During the COVID-19 pandemic, children have had markedly different clinical presentations and outcomes compared to adults. In the acute phase of infection, children are relatively spared the severe consequences reported in adults. Yet, they are uniquely susceptible to the newly described Multisystem Inflammatory Syndrome in Children (MIS-C). This may result from the developmental ‘immunodeficiency’ resulting from a Th2 polarization that starts in utero and is maintained for most of the first decade of life. MIS-C may be due to IgA complexes in a Th2 environment or a Th1-like response to COVID-19 antigens that developed slowly. Alternatively, MIS-C may occur in vulnerable hosts with genetic susceptibilities in other immune and non-immune pathways. Herein, we present a review of the host immune response, virologic and genetic factors, and comparable inflammatory syndromes that may explain the pathophysiology leading to drastic differences in clinical presentation and outcomes of COVID-19 between children and adults.